Control of mini UAV (Unmanned Aerial Vehicle) - Indhumathi (2013)
Unmanned Aerial Vehicle (UAV) has become a popular topic for the research and development. Besides using the UAV for military purpose nowadays the UAVs are using for many using robotic projects. The purpose of this study is to introduce a water dispenser system which is relevant to the actual fire fighter UAV. Both the UAV and the water dispenser system will be discussed in this report.